The Role of Financial Management in Our Galang Bersama Foundation - Lestari Dwi Santi; Vitayanti Fattah; Munawarah; Risnawati (Journal of Humanities, Community Service, and Empowerment, 2025)
Financial management is an important aspect in the operation and sustainability of the Galang Bersama Kami Foundation. This study aims to document and analyze the role of financial management at the Galang Bersama Kami Foundation. The research method used is descriptive qualitative with a single case study approach. Data were obtained through interviews with the foundation's management. The findings indicate that the Galang Bersama Kami Foundation has implemented effective and responsible financial management principles. The results of this study also highlight the importance of financial management in supporting the foundation's goals and missions in improving the quality of life of marginalized communities. By implementing good financial management practices, the foundation can ensure that the funds managed are used efficiently and in accordance with the foundation's goals. This study provides the importance of continuity in improving the foundation's financial management capabilities to support the sustainability of community empowerment programs.